Welded joints machine bodies lightweight and mobile, and other design features - Kowalski, Tadeusz; Walkiewicz, Leszek (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2016)
The paper describes: – design features of machines light and mobile, – minimizing the cost of production machinery of light on the example of welded bodies, – comparison of the structure of bodies welded and cast, – scope and location of the machines in the light sockets and production lines, – example design milling light BĄK for workpieces with small dimensions. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)